Income smoothing: a study of the health sector’s credit unions - Bressan, Valéria Gama Fully; Souza, Douglas Coelho de; Bressan, Aureliano Angel (Review of Business Management, 2017)
Purpose – The aim of this study was to verify whether the credit unions affiliated to Brazilian Confederation of Central Cooperatives (UNICRED) manage their accounting results, in order to reduce the variability of the institution’s returns and transmit a sense of solidity to its members. Design/methodology/approach – The method adopted was the Classic Linear Regression Model with Panel Data, estimated by Feasible Generalized Least Squares for fixed effects and corrections for heteroscedasticity. The sample was made up of 113 credit unions affiliated to UNICRED systems, over the 2001-2011 period, and data was made available by Central Bank of Brazil. Findings – The analysis, carried out through non-discretionary results on credit operations in order to explain the changes in net expenses of provision on credit operations, indicated there was smoothing of results. Thus, we can infer that the credit unions affiliated to UNICRED make use of earnings management in the income smoothing modality. Originality/value – This study contributes to the issue of Accounting Results Management, and corroborates that there are indications that, in the occurrence of higher non-discretionary results, credit unions tend to maximize provisions. Similarly, in the occurrence of lower non-discretionary results, they tend to minimize provisions, making evident the search for smaller variability in results, thus signaling mitigation of risks.